Cyanobacterial Community Structure and Isolates From Representative Hot Springs of Yunnan Province, China Using an Integrative Approach - Keshari, Nitin; Zhao, Yang; Das, Sudipta Kumar; Zhu, Tao; Lu, Xuefeng (Frontiers in Microbiology, 2022)
Cyanobacteria from the representative hot springs of Yunnan Province, China are explored for their diversity and community composition following an integrative approach of cultivation-independent and -dependent studies and further isolation of potential taxa for future biotechnological perspective. 16S rRNA amplicon sequencing of microbial mats in these hot springs with temperature range from 38 to 90°C, revealed Cyanobacteria and Proteobacteria composing a bounteous portion of the bacterial community. The combined approach of 16S rRNA amplicon sequencing and phenotypic analysis revealed the diversity of cyanobacteria (total 45 genera). Out of these a total of 19 cyanobacterial taxa belonging to 6 genera and 10 species were isolated as individuals with prospective of biotechnological exploitations. These isolates were subjected to thorough morphological study and molecular characterization using 16S rRNA gene sequencing for identification and understanding their phylogeny. The identity, phenotypic and genotypic characters of 7 cyanobacterial isolates are not identical to any known cyanobacterial species, generating scope for future taxonomic novelties. Preliminary experiments based on high temperature (50°C) cultivation showed that most of isolates were thermo-tolerant and suggested for their high biotechnological usage potential.